A stunted development analyzing the coverage of the Pandacan Oil Depot issue as seen on online news reports of the Philippine Daily Inquirer, the Philippine Star, and the Manila Bulletin from August 2012 to March 2015 - Vicher, Stela Marie L.; Tangi, Lucia P.; University of the Philippines Diliman. College of Mass Communication (Quezon City University of the Philippines Diliman, 2015)
"The general objective of this research is to study through content and textual analyses how the Inquirer, the Star, and the Bulletin covered the Pandacan oil depot issue through their online news websites from August 2012 to March 2015. Using Agenda-Setting and Media Framing Theories, this study found out how the three media organizations operate under the said theories and how this affected their coverage. By looking into the frequency, location, length, and use of photos or infographs in the news reports, it was established that the three media organizations deemed the issue news-worthy enough to be covered. However, the news websites depended mainly on national and local government officials, leaving little space for the civic groups and residents of Pandacan, thus providing a limited view of the event. Moreover, the coverage heavily relied on source-originated material, making most parts of the reportage permeate only the surface level of the issue. Because of this, the coverage failed to investigate the important aspects of this socioeconomic issue. This dependence on sources also affected the tone of the reportage, which mostly showed a pro-relocation slant."
Vita.
Undergraduate thesis
Keywords: Petroleum industry and trade -- Press coverage; News Web sites -- Philippines; Oil industries -- Philippines